2013
DOI: 10.4049/jimmunol.1202976
|View full text |Cite|
|
Sign up to set email alerts
|

B Cell Activation Is Regulated by the Stiffness Properties of the Substrate Presenting the Antigens

Abstract: B lymphocytes are activated upon Ag sensing by BCRs. The substrate presenting the Ag can show different degrees of stiffness. It is not clear whether B cells can respond to changes in substrate stiffness. In this study we use high-resolution, high-speed live cell imaging techniques to capture the molecular events in B cell activation after the recognition of Ags tethered to polyacrylamide gel substrates with variable degrees of stiffness as quantified by Young’s modulus (2.6–22.1 kPa). We show that the initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
105
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 61 publications
11
105
0
2
Order By: Relevance
“…Enhanced accumulations of BCR and pSyk molecules into the B-cell IS were induced by stiffer substrates. These observations are largely consistent with our previous study [38], showing that the initiation of B-cell activation immediately after BCR-antigen recognition is favored by the antigens tethered on the surface of a stiffer polyacrylamide (PA) gel (22.1 kPa) compared with the case of the antigens on a softer PA gel (2.6 kPa). These observations are also consistent with a recent study by Kam and colleagues investigating the mechanosensing capability of T cells using a PA gel based experimental system [33], showing that the activation of T cells was obviously enhanced upon encountering stiffer substrate, as quantified by the recruitment of pSFK and pZAP70 into IS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Enhanced accumulations of BCR and pSyk molecules into the B-cell IS were induced by stiffer substrates. These observations are largely consistent with our previous study [38], showing that the initiation of B-cell activation immediately after BCR-antigen recognition is favored by the antigens tethered on the surface of a stiffer polyacrylamide (PA) gel (22.1 kPa) compared with the case of the antigens on a softer PA gel (2.6 kPa). These observations are also consistent with a recent study by Kam and colleagues investigating the mechanosensing capability of T cells using a PA gel based experimental system [33], showing that the activation of T cells was obviously enhanced upon encountering stiffer substrate, as quantified by the recruitment of pSFK and pZAP70 into IS.…”
Section: Discussionsupporting
confidence: 92%
“…The cells were then fixed with 4% paraformaldehyde and imaged by confocal fluorescence microscope (Zeiss, LSM710) with a 40× objective water lens or confocal fluorescence microscope (Olympus, OX81) with a 60× objective oil lens. Data were analyzed by Matlab (Mathworks) and Image J (NIH, U.S.) software as indicated previously [38].Imaging the synaptic recruitment of pTyr, pSyk, and pPI3K molecules Recruitment of pTyr, pSyk, and pPI3K into the IS of B1-8 specific J558L cells or mouse primary naïve B cells upon encountering antigens on stiffer or softer PDMS surfaces were imaged after intracellular staining by anti-pTyr (Clone 4G10) antibody, phospho-Zap-70 (Tyr319)/Syk (Tyr352) antibody (Cell Signaling Technology), or anti-pPI3K p85(Y858)/ p55(Y199) antibody as previously described [38]. Briefly, after fixed by 4% paraformaldehyde for 15 min, B cells were treated with 0.1% Triton X-100 for 30 min and blocked with 100 μg/mL goat nonspecific IgG in PBS for 1 h. Then B cells were stained with these signaling molecule specific antibodies for 60 min on ice followed by the staining of secondary antibody Alexa 568 conjugated donkey F(ab') 2 fragment anti-rabbit IgG (H + L) or Alexa 568 conjugated goat F(ab') 2 fragment anti-mouse IgG (Invitrogen).…”
mentioning
confidence: 99%
“…Moreover, both our studies and those of others showed that these accumulation events are sensitive to the biochemical and biophysical features of the antigens that B cells likely encounter in vivo (4,5). These features include but are not limited to antigen density (6,7), antigen affinity (6,7), antigen valency (8)(9)(10)(11)(12)(13), the mobility of the antigen (14)(15)(16)(17), the stiffness of the substrates presenting the antigen (18,19) and the mechanical forces delivered to the BCRs by the antigens (20,21). These facts highlight a long-standing question in immunology: how can the initiation of B-cell activation process the information of antigen specificity, density, affinity, valency, mobility, substrate stiffness, and mechanical forces in such an efficient way?…”
supporting
confidence: 63%
“…The importance of mechanical tension in BCR activation was revealed in experiments showing that B cell responsiveness varies with the stiffness of the antigenic substrates 133 . Antigens presented on stiff substrates, which allow the generation of higher forces on the BCR, promote BCR signalling more efficiently than antigens on softer substrates, which limit tension.…”
Section: [H1] Cytoskeletal Regulation Of Biomechanicsmentioning
confidence: 99%